Bioremediation of Heavy Metal Contaminated Soil using Biosurfactant - Garg, Ishita (My University, 2011)
Bioremediation is an efficient tool practiced now-a-days for the removal of contaminants from the contaminated soil or water. In this report our objective was to remediate arsenic contaminated soil collected from West Bengal using biosurfactant. We have carried out characterization and fractionation of arsenic contaminated soil, biosurfactant production from Pseudomonas aeruginosa, screening of microbial species from soil, lysimeter studies with different treatments for removal of arsenic and collection and characterization of root exudates in presence of arsenic. From the study conducted, it was found that biosurfactant mediated phytoremediation is effective in removing arsenic from soil. It is also found that in presence of arsenic Vetiveria plant produces biosurfactant, with biochemical changes including decrease in carbohydrate content and stable protein content.
M.Tech. (Environmental Science and Technology)
Keywords: Bioremediation